Omorfo Cosmetic / Muhammad Ajwad Zainudin - Zainudin, Muhammad Ajwad (2020)
O’morfo is a cosmetic company under the lines of skincare businesses and being establish by Muhammad Ajwad Bin Zainudin in the aim to help small and medium scale industries or Rosella plantation all across the South East Asia. The name of our company meaning in Greek words as beautiful because of our products that can mimic the beauty effects towards the skin with strengthening the skin barrier to its optimum effect and our slogan for the company is “Together We Slay” as we believe our products can change the organic usage trends in skincare worlds. For now the trend of incorporating Centella asiatica, Yuju fruit and watermelon into the lines become an attention to the customers choices of skincare thus we believe by incorporating Rosella extract will catch the world eyes.